Relativização da coisa julgada em matéria falimentar - Scremin Neto, Ferdinando (2024)
The present thesis seeks to re-signify the institute of res judicata in the light of Brazilian bankruptcy law, in order to highlight the existence of transrescissory defects capable of allowing the bankruptcy to be reversed due to the insubsistence of the assumptions of the judgment constituting the bankruptcy. It uses national and foreign bibliographical research, with a review of court decisions on the subject. In the end, it dares to extend the deadline for reviewing a bankruptcy decision, on the grounds of business protection and the social function of the company, establishing five basic hypotheses for relativization based on insurmountable defects or problems. The approach deals with the corresponding procedural and substantive law institutes in an integrated manner, so as to allow the exegete to have a correct systemic and joint understanding of the bankruptcy institutes and their perfect conformity to the ancillary rules of the process, whose primary purpose is precisely to give life and effectiveness to substantive law. It is well known that, in general, a company finds itself in the context of a crisis when it has economic, financial and patrimonial aspects. The first takes place with a considerable downturn in business - the object of the articles of association, i.e. the commercial purpose of the company, the activities it sets out to carry out. The second relates to the financial crisis, understood as the legal dimension of non-payment. And the third is the crisis of assets, typical of the state of insolvency. It is clear that insolvent companies must fail so that healthy ones are not harmed. But the collapse of good companies is bad for the economy, harmful to society and damaging to the state. If there is no market solution for a company in crisis, it should not benefit from judicial reorganization and should therefore go bankrupt. However, it must be pointed out that, in many cases, the economic structures of the market may not work properly, and the intervention of the Judiciary is necessary, with a view to balancing the various interests that gravitate around the company - jobs, the production and consumption chain, the collection of taxes, the regular development of the production chain and the effects on the economy with the generation of employment, income and social development. This is the aspect of the company's social function, i.e. the role it has to play in the economic scenario. And as such, the state cannot remain inert to the fair protection that the legal system confers on it. In cases where the market could have solved business crises and didn't, it offends the sense of justice to think that the end of jobs, the breakdown of the supply network, the cascading effect on medium and small companies dependent on the bankrupt company and the disruption of the economic chain are imposed without there being legal mechanisms to remedy the undue breakdown. In this respect, res judicata cannot be an end in itself. The dogma of res iudicata can perpetuate situations of extreme injustice, in clear offense to the principles of preserving the company and its inherent social function. Not to mention the negative self-image of the entrepreneur, especially in Brazilian culture, due to the Roman-Germanic legal tradition. So it is necessary to check the constitutional principles together, as well as weigh up the principles inherent in bankruptcy and reorganization law, based not only on the risk of the enterprise, but also on the social impact of the company's crisis and the transparency of bankruptcy proceedings and legal certainty itself, since the justice system cannot condone error, fraud and deception. There are therefore three concentric circles around the company, the first and most central inherent to the interests of entrepreneurs; the second tangential to the inspirations of byholders and the last, in this sequence, inherent to the diffuse and collective interests correlated to maintaining the source of production. The legal mechanisms for preventing and dealing with business crises are aimed not only at individual entrepreneurs, but also at all the meta-individual interests inherent in the continuity of the business. Ultimately, it is a question of reframing the institute of res judicata in bankruptcy, making it more in line with the idea of justice and systemic coherence in the legal system.